METONIMI PANDERAN “PEMBICARAAN” DI WARUNG BAHASA BANJAR - Rissari Yayuk (Multilingual, 2019)
The research that will be raised is the metonymy of the "speaking" in the Banjar language in a traditional store (warung). Issues discussed included how the metonym structure of the "speaking" in Banjar was in store? The purpose of this study is to describe the metonym of the Banjar language "conversation" in the warung. The method used is descriptive method with a semantic approach. Data collection is done through reference and recording techniques. The author takes three steps of work, namely the stage of data collection, data processing, and the stage of presenting the results of data analysis. The data analysis technique is the distribution method. The presentation of data analysis describes conversations containing metonymy in Banjar language. Data presentations are written in ordinary words. The population of this study is the Banjar community located in the Gambah neighborhood, South Hulu Sungai Regency, South Kalimantan Province. The time of data collection is from January 2017 to March 2017. The results of this study include metonymy based on part elements with the whole, metonymy based on place attributes, metonymy based on objects for content or function and metonymy based on time attributes.Penelitian yang akan diangkat adalah metonimi panderan “pembicaraan” di warung bahasa Banjar. Masalah yang dibahas meliputi bagaimana struktur  metonimi panderan “pembicaraan” berbahasa Banjar di warung? Tujuan penelitian ini adalah mendeskripsikan struktur metonimi panderan “pembicaraan” di warung bahasa Banjar. Metode yang digunakan adalah metode deskriptif dengan pendekatan semantik. Pengumpulan data dilakukan melalui teknik simak dan catat. Penulis menempuh tiga langkah kerja, yaitu tahap pengumpulan data, pengolahan data, dan tahap penyajian  hasil analisis data. Teknik analisis data adalah metode agih. Sajian analisis data mendeskripsikan ujaran yang mengandung makna metonimi dalam bahasa Banjar. Penyajian data ditulis dengan kata-kata biasa. Populasi penelitian ini adalah masyarakat Banjar yang berlokasi  di lingkungan Gambah, Kabupaten Hulu Sungai Selatan, Provinsi Kalimantan Selatan.Waktu pengambilan data dari bulan Januari 2017 sampai dengan bulan Maret 2017. Hasil penelitian meliputi metonimi berdasarkan unsur bagian dengan keseluruhan, metonimi berdasarkan atribut tempat, metonimi berdasarkan objek untuk isi/fungsi dan metonimi berdasarkan atribut waktu.